Improved indoor air quality during desert dust storms: The impact of the MEDEA exposure-reduction strategies - Achilleos, Souzana; Michanikou, Antonis; Kouis, Panayiotis; Papatheodorou, Stefania; Panayiotou, Andrie G.; Kinni, Paraskevi; Mihalopoulos, Nikos; Kalivitis, Nikos; Kouvarakis, Giorgos; Galanakis, Emmanouil; Michailidi, Eleni; Tymvios, Filippos; et al. (My University, 2023)
Desert dust storms (DDS) are natural events that impact not only populations close to the emission sources but also populations many kilometers away. Countries located across the main dust sources, including countries in the Eastern Mediterranean, are highly affected by DDS. In addition, climate change is expanding arid areas exacerbating DDS events. Currently, there are no intervention measures with proven, quantified exposure reduction to desert dust particles. As part of the wider "MEDEA" project, co-funded by LIFE 2016 Programme, we examined the effectiveness of an indoor exposure-reduction intervention (i.e., decrease home ventilation during DDS events and continuous use of air purifier during DDS and non-DDS days) across homes and/or classrooms of schoolchildren with asthma and adults with atrial fibrillation in Cyprus and Crete-Greece. Participants were randomized to a control or intervention groups, including an indoor intervention group with exposure reduction measures and the use of air purifiers. Particle sampling, PM10 and PM2.5, was conducted in participants' homes and/or classrooms, between 2019 and 2022, during DDS-free weeks and during DDS days for as long as the event lasted. In indoor and outdoor PM10 and PM2.5 samples, mass and content in main and trace elements was determined. Indoor PM2.5 and PM10 mass concentrations, adjusting for premise type and dust conditions, were significantly lower in the indoor intervention group compared to the control group (PM2.5-intervention/PM2.5-control = 0.57, 95% CI: 0.47, 0.70; PM10-intervention/PM10-control = 0.59, 95% CI: 0.49, 0.71). In addition, the PM2.5 and PM10 particles of outdoor origin were significantly lower in the intervention vs. the control group (PM2.5 infiltration intervention-to-control ratio: 0.49, 95% CI: 0.42, 0.58; PM10 infiltration intervention-to-control ratio: 0.68, 95% CI: 0.52, 0.89). Our findings suggest that the use of air purifiers alongside decreased ventilation measures is an effective protective measure that reduces significantly indoor exposure to particles during DDS and non-DDS in high-risk population groups.
Keywords: Air purifier; HEPA; Indoor air quality; Intervention measures; PM